2010
DOI: 10.1182/blood.v116.21.125.125
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb Complex Group Gene Mutations and Their Prognostic Relevance In 5-Azacitidine Treated Myelodysplastic Syndrome Patients

Abstract: 125 Polycomb gene complex mutations have been implicated in the pathogenesis of myeloid neoplasms. ASXL1, a epigenetic regulator of transcription by recruiting polycomb and trithorax complexes to the chromatin domain and EZH2 (histone methyltransferase) is the catalytic domain of polycomb repressive complex (PRC) 2, causing gene silencing by trimethylation of lysine 27 of histone 3(H3K27). To identify the role of mutations in ASXL1, EZH2 and their interaction with other mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“… 8 , 37 The correlation between the presence of mutations in several epigenetic interfering genes (for example, TET2 , EZH2 , ASXL1 and DNMT3 ) and response to AZA has been shown but must be further confirmed to determine clinical applicability. 9 , 10 , 38 Only eight of the 35 MDS patients analyzed in our study had mutated TET2 . As expected, there was no correlation with mutational status and OS, but we could not observe higher rates of response to AZA in mutated cases, most probably because of numerical limitations.…”
Section: Discussionmentioning
confidence: 86%
“… 8 , 37 The correlation between the presence of mutations in several epigenetic interfering genes (for example, TET2 , EZH2 , ASXL1 and DNMT3 ) and response to AZA has been shown but must be further confirmed to determine clinical applicability. 9 , 10 , 38 Only eight of the 35 MDS patients analyzed in our study had mutated TET2 . As expected, there was no correlation with mutational status and OS, but we could not observe higher rates of response to AZA in mutated cases, most probably because of numerical limitations.…”
Section: Discussionmentioning
confidence: 86%
“…Efforts to identify molecular markers of response to therapy have also been made, with TET2 and DNMT3A mutations having been associated with better response to azacytidine, albeit with contradictory data regarding their impact on OS (Traina et al , ). Polycomb complex gene mutations have also been associated with longer survival after hypomethylating therapy (Kulasekararaj et al , ).…”
Section: Closing the Gap With The Clinic: Therapeutic Implicationsmentioning
confidence: 99%
“…Truncated ASXL1 protein is unable to bind methylated histone lysines or interact with other chromatin modifiers (Acquaviva et al , ). A common frameshift mutation (Gly646TryfsX12) in ASXL1 accounting for >50% of mutations in MDS (Abdel‐Wahab et al , ), has been suggested to be a technical artefact; however, analysis of respective constitutional DNA and a large cohort of healthy individuals confirmed this variant as somatic (Kulasekararaj et al , ; Grossmann et al , ).…”
Section: Molecular Karyotyping In Mdsmentioning
confidence: 99%